Gender Dependency and Cultural Independency of Science Interest in an Open and Distant Science Learning Environment - Baram-Tsabari, Ayelet; Kaadni, Alaa (International Review of Research in Open and Distributed Learning, 2009)
This study aims to describe the similarities and differences in the science interests of males and females from Israeli and Arab Middle Eastern countries, as derived from over 1,000 science questions sent to an international ask-a-scientist site. Our findings indicate that while the stereotypical gender gap in interest persists, and significant differences were found between the age groups, no significant differences were found between science questions that were sent by Israelis and Arabs. Furthermore, no correlation was found between female participation and the state of gender equity in the country, and only 1% of the questions made any reference to country-specific, local, or religious aspects. One may conclude that science interests are gender- and age-dependent but culturally-independent in this asynchronous, open and distant science learning environment. Further research is needed in order to determine if this is a genuine attribute of science interest in ODL environments or an outcome of the digital divide in the region.